Nivel de información y ansiedad del familiar cuidador del adulto en la unidad de cuidados intensivos - Fernández Narváez, Sara Celice (2017)
This research study descriptive correlational type, cross-sectional, conducted in the months of June and July 2015 in order to determine the relationship between the level of information provided by the nurse and the level of anxiety of the relatives of the patients hospitalized in the intensive care unit of the Regional teaching Hospital of Trujillo. The sample population was constituted by 80 relatives who met the inclusion and exclusion criteria. For data collection, two formats were used a questionnaire on the level of information provided by the nurse and a scale for assessing the level of anxiety of the relative. For the statistical analysis the chi-square test was used, it was considered (P < 0.05). The results were presented in one-and double-entry statistical tables, numerically and percentage. It is concluded that 80% of relatives presented a regular level of information and 60% presented a moderate level of anxiety. There is a significant relationship between the level of information and the level of anxiety of the relatives of hospitalized patients in the intensive care unit.